Kepemimpinan Kepala Madrasah Dalam Meningkatkan Kinerja Guru Di MAS Islamiyah Tamiang Mandailing Natal - Hayati, Mirna; Junaidi, Junaidi; Aprison, Wedra; Kamal, Muhiddinur (STAI Denpasar Bali, 2024)
This research aims to reveal the role of madrasa head leadership in improving teacher performance at MAS Islamiyah Tamiang. The research background illustrates the importance of educational leadership in achieving the effectiveness and efficiency of educational institutions. The focus of the research is on the duties and functions of the madrasa head in Learning Management (PBM) at Madrasah Aliyah Islamiyah Tamiang. The research method used is field research with a qualitative approach. Data was collected through interviews, field notes, documentation and observation. The research results show that madrasa heads play an active role in improving teacher performance by involving them in training, training, seminars and other activities. Routine supervision is carried out to accompany and improve the teaching and learning process. Apart from that, the madrasah principal provides motivation, rewards, and includes teachers in workshops to improve professional competence. The research conclusion shows that the leadership of the madrasa head has a positive impact on teacher performance. The madrasa head carries out his role by involving teachers in various activities that support competency development. However, the research also identified several weaknesses in the supervision of teacher discipline and use of time, as well as suggestions for improving the optimization of supervision by madrasah heads.